245 ps-TOF brain-dedicated PET prototype with a hemispherical detector arrangement. (14th July 2020) - Yoshida, Eiji; Tashima, Hideaki; Akamatsu, Go; Iwao, Yuma; Takahashi, Miwako; Yamashita, Taichi; Yamaya, Taiga
Abstract: Brain PET, which has led research in molecular imaging and diagnosis of brain cancer, epilepsy and neurodegenerative disorders, is being spotlighted again to promote earlier diagnosis of dementia with the advent of amyloid and tau tracers. To meet this demand, in this paper, we developed a brain-dedicated PET imaging device with a hemispherical detector arrangement, which provides comparable sensitivity with fewer detectors than conventional cylindrical geometries. The introduction of the time-of-flight (TOF) measurement capability was a key point for the development to get a gain in the image signal-to-noise ratio. Currently, whole-body PET scanners with around 200–400 ps coincidence resolving time (CRT) are commercially available. In order to obtain the same TOF gain which can be obtained with 400 ps CRT for a 30 cm diameter object, 267 ps CRT will be required for a 20 cm diameter object such as the human head. In this work, therefore, we aimed at developing a TOF brain-dedicated PET prototype with the hemisphere detector arrangement and the CRT faster than 267 ps. The detector was composed of a 12 × 12 lutetium fine silicate (LFS) array coupled with a 12 × 12 multi-pixel photon counter (MPPC) array. Each LFS crystal with a size of 4.14 × 4.14 × 10 mm 3 was individually coupled to a separate MPPC. Singles list-mode data from each detector were stored, and coincidences were identified using a coincidence-detection software algorithm. The CRT of 245 ps was finally achieved as the system average after a fine timing correction. For image reconstruction, we implemented the list-mode TOF-OSEM. For a small rod phantom, rods of 3 mm diameter were clearly separated. Also, images of the 3D Hoffman brain phantom, which demonstrated clear contrast between gray and white matter, supported the effect of TOF information.